Lost and Othered Children in Contemporary Cinema - Olson, Debbie C.; Scahill, Andrew (Lexington Books, 2012)
Children have been a part of the cinematic landscape since the silent film era, yet children are rarely a part of the theoretical landscape of film analysis. Lost and Othered Children in Contemporary Cinema, edited by Debbie C. Olson and Andrew Scahill, seeks to remedy that oversight. Throughout the over one-hundred year history of cinema, the image of the child has been inextricably bound to filmic storytelling and has been equally bound to notions of romantic innocence and purity. This collection reveals, however, that there is a body of work that provides a counter note of darkness to the traditional portraits of sweetness and light. Particularly since the mid-twentieth century, there are a growing number of cinematic works that depict childhood has as a site of knowingness, despair, sexuality, death, and madness. Lost and Othered Children in Contemporary Cinema challenges notions of the innocent child through an exploration of the dark side of childhood in contemporary cinema. The contributors to this multidisciplinary study offer a global perspective that explores the multiple conditions of marginalized childhood as cinematically imagined within political, geographical, sociological, and cultural contexts.